2013
DOI: 10.2337/dc13-0450
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Diabetic Nephropathy

Abstract: OBJECTIVEDiabetic nephropathy (DN) is a leading cause of end-stage renal disease (ESRD). Obstructive sleep apnea (OSA) is common in type 2 diabetes and increases oxidative stress. Hence, OSA could promote the development and progression of DN.RESEARCH DESIGN AND METHODSThis was a cohort study in adults with type 2 diabetes. Patients with known OSA or ESRD were excluded. DN was defined as the presence of albuminuria or an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2. DN progression was based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
126
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 41 publications
6
126
1
Order By: Relevance
“…We previously reported that OSA is associated with peripheral neuropathy, nephropathy, and estimated glomerular filtration rate decline in patients with T2D independently of obesity (10,11). We also previously showed that OSA is independently associated with increased nitrosative and oxidative stress as well as impaired microvascular regulation in patients with T2D (10).…”
mentioning
confidence: 99%
“…We previously reported that OSA is associated with peripheral neuropathy, nephropathy, and estimated glomerular filtration rate decline in patients with T2D independently of obesity (10,11). We also previously showed that OSA is independently associated with increased nitrosative and oxidative stress as well as impaired microvascular regulation in patients with T2D (10).…”
mentioning
confidence: 99%
“…123 The progression to albuminuria was numerically but not statistically greater in patients with OSA compared those without OSA (22.6 % versus 13.3 %; p=0.23). 123 In the same observational longitudinal study the use of CPAP was associated with a favourable impact on eGFR decline over the follow-up In a study of Japanese patients with T2D, an ODI≥5 was independently associated with microalbuminuria in women but not in men after adjustment for confounders. 124 Another cross-sectional study showed no relationship between OSA and microalbuminuria in patients with T2D, but this study was of a small sample size (n=52).…”
mentioning
confidence: 97%
“…moderate to severe OSA) and OSA was an independent predictor of study end eGFR (B=−4.2; p=0.03) and eGFR decline. 123 Baseline AHI was also an independent predictor of study end eGFR after adjustment (B= −4.6, p=0.02). 123 The progression to albuminuria was numerically but not statistically greater in patients with OSA compared those without OSA (22.6 % versus 13.3 %; p=0.23).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The potential causative role of OSA in the development of these important comorbidities is the subject of recent dedicated reviews in the Journal of Thoracic Disease (7,86), and will not be discussed in detail here. Notably, OSA may hasten the development of diabetic nephropathy (DN), as evidenced by an increased prevalence of OSA in subjects with DN, and an increased rate of progression of CKD in OSA patients, in a cohort of 224 type 2 diabetes followed over 2.5 years (87).…”
Section: Conventional Ckd Risk Factors and Osamentioning
confidence: 99%